2006
DOI: 10.1103/physreva.73.062336
|View full text |Cite
|
Sign up to set email alerts
|

Creation of entanglement in a scalable spin quantum computer with long-range dipole-dipole interaction between qubits

Abstract: Creation of entanglement is considered theoretically and numerically in an ensemble of spin chains with dipole-dipole interaction between the spins. The unwanted effect of the long-range dipole interaction is compensated by the optimal choice of the parameters of radio-frequency pulses implementing the protocol. The errors caused by ͑i͒ the influence of the environment, ͑ii͒ nonselective excitations, ͑iii͒ influence of different spin chains on each other, ͑iv͒ displacements of qubits from their perfect locatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…In [47], it was shown that dynamic magnetic responses in dipolar spinor condensates are characterized by long-range magnetic dipoledipole interactions with evident properties of macroscopic entanglement. An ensemble of spin chains with dipole-dipole interactions between the spins was analyzed in [48]. It was shown that when a spin-chain system with a long-range dipoledipole interaction is placed into a non-homogeneous external magnetic field, entanglement can occur.…”
Section: Introductionmentioning
confidence: 99%
“…In [47], it was shown that dynamic magnetic responses in dipolar spinor condensates are characterized by long-range magnetic dipoledipole interactions with evident properties of macroscopic entanglement. An ensemble of spin chains with dipole-dipole interactions between the spins was analyzed in [48]. It was shown that when a spin-chain system with a long-range dipoledipole interaction is placed into a non-homogeneous external magnetic field, entanglement can occur.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that a one-dimensional arrangement of spins in a linear qubit register will provide the highest degree of interaction control, and this arrangement has been at the focus of theoretical proposals for endohedral fullerenes. 25,26,35,44,39,40,45,41,46 A linear chain also provides a simple means to make every qubit addressable when a magnetic field gradient is applied along the chain direction. 39 Taking as the direction of the external For 'Endofullerenes: electron transfer and spin' (A.…”
Section: Spin-spin Interactions and The Linear Qubit Registermentioning
confidence: 99%